O mercado de helicópteros no Brasil: atributos determinantes na escolha do modelo de aeronave - Oliveira, Marcelo Madruga de (2016)
In the current context, the life cycle of a lot of products becomes increasingly smaller, given the speed of technology change nowadays. In this scenario, the helicopter market is configured as an exception to the rule. With an average time for project development of eight (08) years and operating period of no less than thirty (30) years, they end up generating major challenges to their manufacturers. Those manufacturers face the difficult task of meeting the needs of its customers, before their products become obsolete, respecting the limits of sale imposed by the market value. Thus, it is vital to have, within the marketing strategy in the companies, the most accurate knowledge of those attributes which are relevant to the buyers. Through this knowledge, different manufacturers seek to provide their products with elements able to ensure the long life expected. In this sense, the present study, whose area of concentration lies in consumer marketing, aims to identify the key attributes related to the choice of a particular helicopter model. The methodology used two surveys, a qualitative and a quantitative, applied to pilots and maintenance heads. Its scope is limited to the Brazilian market of helicopters, civil sector (executive) nowadays. Through an exploratory approach, it is expected to identify attributes in defining the process of choosing an aircraft. These points will allow the development of specific marketing strategies, product development and support. Therefore, it is expected to answer the demands of this public, ensuring the expected longevity of the product and a competitive advantage over their competitors.